The Importance of Sulfur in Ruminant Nutrition - Svetlana Malyugina (Scientific Papers Animal Science and Biotechnologies, 2023)
Sulfur (S) is one of the basic building elements; after calcium and phosphorus, it is the third most abundant mineral in the human body. Sulfur is also essential in animal nutrition. It has long been recognized that S represents an essential element for rumen microbes and is closely related to nitrogen metabolism. Sulfur is an important constituent of amino acids, enzymes, and vitamins in humans and animals. Sulfur is a component of various organic nutrients required by ruminants. It is crucial for producing certain enzymes, vitamins, hormones, and amino acids in the rumen, including cystine, methionine, and cystine. Sulfur amino acids, for instance, are found in collagen, the primary structural protein in mammalian tissues. Also, sulfur is not stored in the body. Therefore, it needs to be presented in animal diets in order to maintain the synthesis of these nutrients in the rumen. In ruminants, sulfur supplementation is essential for overall health, growth and production, amino acid balance, and wool quality. Despite this, excessive sulfur digestion may cause a toxic effect on animals and adversely affect animals' performance and health, even causing serious diseases such as polioencephalomalacia (PEM). High sulfur levels in diets can significantly reduce animal performance, decrease milk production and sometimes even result in death. This article will focus on current knowledge about the metabolism and role of sulfur in the ruminant, factors affecting the production of hydrogen sulfide in the rumen, and the potential mechanisms behind sulfur toxicity in cattle. Additionally, possible strategies for minimizing sulfur toxicity in cattle diets will be discussed.